ANALISIS DAYA TARIK LATTE ART TERHADAP MINAT PEMBELIAN DI COFFE SHOP KOTA BOGOR - Rahmat Hidayat; Theodorus Ezra Indrawan (Bogor Hospitality Journal, 2021)
Coffee as the Coffee Shop's superior product can have added value, one of which is through the expertise and creations of coffee mixters (baristas) who serve coffee with the addition of Latte Art. This study aims to analyze the effect of Latte Art's Attractiveness to Purchase Interest at the Coffee Shop in Bogor City. The number of samples used in this study were 30 respondents at the Coffee Shop in Bogor City. Data was collected using a questionnaire with a non-probability sampling technique and direct observation at the Coffee Shop in Bogor City. Meanwhile, the non-probability sampling technique used in this study was accidental sampling. The research data were analyzed using a statistical application program on a computer, namely the SPSS version 16.0 program. The scientific method used in this research is a descriptive method with a quantitative approach. Data were analyzed using descriptive analysis, Pearson Product Moment correlation coefficient test, Kolmogorov-Smirnov normality test, simple linear regression analysis and partial significance test (t test). Based on the results of simple regression equation analysis, it can be seen that Latte Art Products have a significant effect on Purchase Interest at the Coffee Shop in Bogor City. The results of the t-test indicate that the t-count value is greater than the t-table (3.797 > 2.04841) and the significance value (0.001) is smaller than the 5% significance level. Thus, the Latte Art product is stated to have a significant effect on Purchase Interest at the Coffee Shop in Bogor City and the alternative hypothesis (H1) is accepted.